Effect of Cold Storage Duration on the Quality of Super Red (Hylocerus costaricensis) and White (Hylocerus undatus) Dragon Fruits - Fahmi Nur Aida Latif; Yulita Nurchayati; Endah Dwi Hastuti (The University of Lampung, 2025)
Postharvest storage is carried out to control the metabolic rate so the quality of fruits can be maintained properly until it reaches the costumers. Cold storage can reduce metabolic reactions, such as respiration and transpiration. However, storing too long in cold temperatures can cause the quality of the fruit to deteriorate. Each type of dragon fruit has different chemical contents that will affect the quality of fruits after storage. This study aims to determine the effect of the type of dragon fruit, cold storage duration, and interaction between the two treatments. Both type of dragon fruit are packed in PP plastic and then stored at 10°C. Observation were made at different storage durations. This study used RAL, with the first being super red and white dragon fruits. The second factor was storage duration of 0, 7, 14, and 21 days. Data were analyzed using ANOVA and continued with DMRT if it had a significant effect. The result of the study showed that the treatment of fruit type had significant effect on antioxidant activity, vitamin C content, and total sugar level. Storage duration treatment had significant effect on antioxidant activity and vitamin C content. Keywords: Antioxidant activity, Cold storage, Dragon fruit, Post-harvest, Vitamin c.